(untitled) (International Journal of Emerging Trends in Science and Technology, 2017)
Cartesian product of two manifolds has been defined and studied by Pandey[2]. In this paper we have taken Cartesian product of k-Hsu-Structure manifolds, where k is some finite integer, and studied some properties of curvature and Ricci tensor of such a product manifold.